Efektivitas Pengelolaan Dana Zakat Produktif Baznaz dalam Mengentaskan Kemiskinan di Desa Melayu Kecamatan Lambu Kabupaten Bima - Ariyansyah; Umar Sagaf; Muhammad Yunan Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the effectiveness of productive zakat management by BAZNAS in alleviating poverty in Malay Village, Lambu District, Bima Regency and analyze the contribution of productive zakat to poverty alleviation in Malay Village, Lambu District, Bima Regency. The method used is descriptive qualitative through interviews and observations of mustahik. The results show that productive zakat management by BAZNAS Bima Regency in Malay Village has proven its effectiveness in poverty alleviation through a sustainable economic empowerment approach based on the Bank Zakat Mikro (BZM) scheme. The program has succeeded in transforming mustahiqs into independent business actors in the livestock and handicraft sectors, with concrete achievements in the form of a 30% increase in income per year, transformation of the status of 15 families from mustahiqs to muzakki, and a 12% reduction in the poverty rate in three years. Supported by systematic governance and multi-stakeholder collaboration that utilizes local potential, this program overcomes the challenges of financial literacy and market access to create economic independence, proving productive zakat as a transformative instrument that is not only charitable but also empowering in a sustainable manner.